EVALUASI LEVEL OF SERVICE MELALUI KONFIGURASI SPASIAL BERBASIS SPACE SYNTAX PADA TERMINAL 3 DOMESTIK SOETTA (Jurnal Arsitektur ARCADE, 2026)
This study aims to evaluate the relationship between spatial configuration and Level of Service (LoS) within the domestic terminal using the Space Syntax approach and IATA Airport Development Reference Manual (ADRM) 12th Edition. The research employed a quantitative-descriptive method through Visibility Graph Analysis (VGA) using DepthmapX to assess spatial integration, connectivity, and intelligibility across the main passenger processing areas, including check-in hall, security checkpoint, boarding lounge, baggage claim hall, and arrival hall. LoS evaluation was conducted based on peak hour passenger demand, queue capacity, processing time, and spatial capacity standards. The results indicate that the terminal has a strong linear spatial structure with high integration values along the main circulation corridors, supporting efficient passenger movement and orientation. However, several high-demand areas, particularly the check-in hall and baggage claim hall, still experience sub-optimum operational performance despite having adequate spatial capacity. The study concludes that effective terminal performance is influenced not only by spatial configuration but also by operational processing capacity and passenger flow distribution.